The treasure revealer of Bhutan: Pemalingpa, the Terma tradition and its critics - Tshewang, Padma (Bibliotheca himalayica / 3, 1995)
Predominantly on biography of a Bhutanese treasure reveler Gter-ston Padma-gliṅ-pa, b. 1450?, Rñiṅ-ma-pa lama